Indonesia, Debt Burden and Development in the Era of Joko Widodo: A Critical Note - Herdi Sahrasad (Jurnal Peradaban, 2024)
Indonesia's economy under Jokowi confronts severe corruption and an escalating debt burden. The populace confronts a deterioration in economic growth and purchasing capacity. Indonesia faces the risk of becoming a "systemically failed state" due to its excessive debt payments outpacing its allocation for healthcare and education, according to UN Secretary General Antonio Guterres. Sri Mulyani Indrawati, Indonesia's Minister of Finance, stated that 40% of the population would be classified as impoverished according to the World Bank's poverty threshold. This is the PPP value, denoting purchasing power parity. Developing nations in Southeast and South Asia, along with the remainder of Asia, are on the brink of an economic catastrophe, prompting a warning from the UN. More severe than the crises of 2008 and the COVID-19 pandemic of 2020, as stated by the international organization.